DISEASE RECURRENCE PREDICTORS FOR PATIENTS WITH HEAD AND NECK SQUAMOUS CELL CARCINOMA - Yuniardini S. Wimardhani; D. M. Walker; J. R. Gibbins; M. J. Veness; G. J. Morga; I. I. Kalains (Journal of Dentistry Indonesia, 2015)
Information on reliable factors to predict patient outcome is important for deciding upon the best treatment to increase loco-regional control, overall survival and quality of life of patients with head and neck squamous cell carcinoma (HNSCC). The objective of this study was to investigate the role of clinico-pathological parameters as predictors of disease recurrence in patients with HSNCC. We studied fifty patients who were seeking treatment for primary HSNCC in Westmed Hospital between 2002 – 2004. Univariate analysis was used to identify any significant association between clinico-pathological parameters and disease recurrence. It was showed that age (p=0.008), cTNM stage (p=0.02), size of tumour (p=0.009) and positive tumour margin (p=0.002) predicted the risk of the development of disease recurrence. A longer follow-up study should be performed to assess the significance of these factors on overall survival as well as separate studies on prognostic indicators for patients with histologically negative lymph node.